European‐American and African‐American Mothers' Emotion Socialization Practices Relate Differently to Their Children's Academic and Social‐emotional Competence. Issue 3 (12th October 2012) - Nelson, Jackie A.; Leerkes, Esther M.; Perry, Nicole B.; O'Brien, Marion; Calkins, Susan D.; Marcovitch, Stuart
Abstract The current study examines whether the relation between mothers' responses to their children's negative emotions and teachers' reports of children's academic performance and social‐emotional competence are similar or different for European‐American and African‐American families. Two hundred mothers (137 European‐American, 63 African‐American) reported on their responses to their five‐year‐old children's negative emotions and 150 kindergarten teachers reported on these children's current academic standing and skillfulness with peers. Problem‐focused responses to children's negative emotions, which have traditionally been considered a supportive response, were positively associated with children's school competence for European‐American children, but expressive encouragement, another response considered supportive, was negatively associated with children's competence for African‐American children. The findings highlight the need to examine parental socialization practices from a culturally specific lens.